2021
DOI: 10.3390/ijms22116077
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs in Kidney Diseases: The Long and Short of Them

Abstract: Recent progress in genomic research has highlighted the genome to be much more transcribed than expected. The formerly so-called junk DNA encodes a miscellaneous group of largely unknown RNA transcripts, which contain the long non-coding RNAs (lncRNAs) family. lncRNAs are instrumental in gene regulation. Moreover, understanding their biological roles in the physiopathology of many diseases, including renal, is a new challenge. lncRNAs regulate the effects of microRNAs (miRNA) on mRNA expression. Understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 117 publications
(138 reference statements)
0
17
0
Order By: Relevance
“…For example, our group revealed an exosomal miRNA signature associated with albuminuria in hypertension [ 29 ]. The lncRNA group has reached special relevance in the last years in health and diseases, but few studies have reported on the role of lncRNA in renal pathology [ 12 , 17 ]. In recent years, another ncRNA group, piRNAs, have gained prominence as modulators of disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our group revealed an exosomal miRNA signature associated with albuminuria in hypertension [ 29 ]. The lncRNA group has reached special relevance in the last years in health and diseases, but few studies have reported on the role of lncRNA in renal pathology [ 12 , 17 ]. In recent years, another ncRNA group, piRNAs, have gained prominence as modulators of disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…NcRNAs can be divided into three categories based on their length: ncRNAs longer than 200 nucleotides (nt), including ribosomal RNA (rRNA) and long non-coding RNA (lncRNA); ncRNAs between 40 nt and 200 nt, such as transfer RNA (tRNA), small nucleolar RNA (snoRNA) and small nuclear ribonucleic acid RNA (snRNA); and ncRNA shorter than 40 nt, such as microRNA (miRNA), piwi-interacting RNA (piRNA) and small interfering (siRNA) [ 8 , 9 ]. NcRNAs’ expression is tissue and cell-type specific under physiological conditions and plays an important role in many biological processes by regulating gene expression at epigenetic, transcriptional and post-transcriptional levels [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we show in a large cohort that the alterations in miR-126 levels are correlated with markers of endothelial dysfunction and cardiovascular disease, further expanding knowledge on the physiopathology of this non-coding RNA in CKD. In the future, long non-coding RNAs can also be developed as better biomarkers of CKD, as they are known to be more tissue-specific than miRNAs [39].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lncRNAs may be useful as potential biomarkers for the early diagnosis and prognosis of many diseases, including patients with CKD. The review summarizing the role of lncRNAs in kidney diseases, and their function as prognostic biomarkers has recently been published [ 40 ].…”
Section: Key Concepts Of Proteomics In Disease Analysismentioning
confidence: 99%